Nutritional status of Bali Rugby Team athletes preparing for PON Papua 2021 - I Putu Agus Dharma Hita; B.M. Wara Kushartanti; Doni Pranata; Widiyanto Widiyanto (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
Nutritional status is an important factor in maintaining body immunity. Poor nutritional status is one of the causes of degenerative diseases caused by a damaged lifestyle. This study aims to determine the nutritional status of Bali Rugby team athletes in preparation for the 2021 National Sports Week (PON) held in Papua Province. The type of research used is descriptive quantitative research with a survey method. The sample of this study was 14 athletes from the Bali Rugby Team, with an average age of 20 years. The data collected were height and weight and then analyzed using the Body Mass Index (BMI) formula. The results of this study are the average nutritional status of the Bali Rugby team athletes in preparation for PON Papua 2021, namely in the obesity category I, with details of the normal category as many as 5 athletes (35.7%), overweight category as many as 3 athletes (21.4%), and obesity category I as many as 6 athletes (42.9%). The conclusion in this study is that the average nutritional status of Bali Rugby team athletes in preparation for the 2021 National Sports Week (PON) held in Papua Province shows that athletes are in the obesity category I. From these results, it is hoped that the coach can use it as information to face PON 2021. by evaluating a training program that is tailored to the condition of the athlete so that it can produce maximum performance in the Rugby sport in Bali Province. STATUS GIZI ATLET TIM RUGBY BALI PERSIAPAN PON PAPUA 2021 AbstrakStatus gizi merupakan salah satu faktor penting dalam menjaga imunitas tubuh. Status gizi yang buruk adalah salah satu penyebab timbulnya penyakit-penyakit degeneratif yang disebabkan oleh rusaknya gaya hidup. Penelitian ini bertujuan untuk mengetahui status gizi atlet tim Rugby Bali dalam persiapan Pekan Olahraga Nasional (PON) 2021 yang dilaksanakan di Provinsi Papua. Jenis penelitian yang digunakan yaitu penelitian deskriptif kuantitatif dengan metode survei. Sampel penelitian ini merupakan atlit Tim Rugby Bali yang berjumlah 14 orang wanita dengan rata-rata usia 20 tahun. Data yang terkumpul yaitu tinggi badan dan berat badan dan kemudian dianalisis menggunakan rumus Indeks Massa Tubuh (IMT). Hasil dari penelitian ini yaitu rata-rata kondisi status gizi atlet tim Rugby Bali dalam persiapan PON Papua 2021 yaitu dalam kategori obesitas I, dengan rincian kategori normal sebanyak 5 atlet (35,7%), kategori overweight sebanyak 3 atlet (21,4%), dan kategori obesitas I sebanyak 6 atlet (42,9%). Kesimpulan dalam penelitian ini yaitu rata-rata status gizi atlet tim Rugby Bali dalam persiapan Pekan Olahraga Nasional (PON) 2021 yang dilaksanakan di Provinsi Papua menunjukan bahwa atlet termasuk kategori obesitas I. Dari hasil tersebut, diharapkan pelatih dapat menjadikannya sebagai informasi untuk menghadapi PON 2021 dengan cara mengevaluasi program latihan yang disesuaikan dengan kondisi atlet sehingga dapat menghasilkan prestasi yang maksimal pada cabang olahraga Rugby di Provinsi Bali.